Commander in chief : Franklin Delano Roosevelt, his lieutenants, and their war - Larrabee, Eric (A Cornelia and Michael Bessie book, 1987)
Individual chapters describe Roosevelt's relations with George C. Marshall, Ernest Joseph King, Henry Harley "Hap" Arnold, Archer Vandegrift, Douglas MacArthur, Chester W. Nimitz, Dwight D. Eisenhower, Joseph Warren Stilwell, and Curtis E. LeMay.